Evaluation of the physical-chemical composition and hypoglycemic properties in biscuits produced with eggplant (Solanum melongena L.) and okra (Abelmoschus esculentus L. Moench) - Oliveira, Thayse Wilma Nogueira de (2020)
This study aimed to evaluate the physical-chemical composition and hypoglycemic properties of okra and eggplant flours. Initially, the vegetables were dehydrated, crushed to the point of flour, conditioned and stored until use. The flours were subjected to physical-chemical evaluation to determine the moisture, lipids, proteins, carbohydrates and polyphenols contents and, then, the experimental analysis was carried out. This was done using Swiss mice, distributed in 6 groups (n = 3), one healthy, two diabetic controls and three diabetics treated with commercial diets containing eggplant flour, okra and the mixture of the two flours. The survey lasted 20 days, with daily measurement of water and food and, in the interval of 5 days, blood glucose and weight. The research was approved by the Animal Experimentation Ethics Committee of the same institution, under protocol number 157/16. Statistical analysis was performed using STATISTICA Software version 7.0. The results showed that the flours have an important nutritional composition, mainly in terms of fiber content. In relation to functional activity, okra flour was able to significantly reduce the glycemia of mice when compared to eggplant flour, a result comparable to that of other authors, who emphasize the importance of fibers and bioactive compounds in obtaining this result. both flours had a good nutritional composition, but the okra was more efficient in reducing the glycemia of diabetic mice, and may become an alternative in the dietary treatment of this pathology.